Chemical characterization, antimicrobial, and antioxidant potentials of Juniperus phoenicea wood tar - Sadia Tina; Oussama Khibech; Samy Iskandar; Mohamed Bouhrim; Mohammed Al-zharani; Fahd A. Nasr; Ashraf Ahmed Qurtam; Allal Challioui; Balouch Lhousaine; Meryem El Jemli (PLoS ONE, 2026)
Wood tar obtained from Juniperus phoenicea L. is traditionally used in Morocco, yet its chemical profile and biological activities remain insufficiently documented. In this work, Juniperus phoenicea wood tar ( JPWT ) was chemically characterized by GC-MS, qualitatively screened for major phytochemical classes, and evaluated for total polyphenols, tannins and flavonoids contents. Antioxidant activity was assessed using DPPH and FRAP assays, and antibacterial activity was screened by the disc diffusion method. GC-MS identified 17 compounds, with hydroxychavicol (46.3%), 2,3-dehydroferruginol (18.5%) and eugenol (7.3%) as major constituents. JPWT showed high levels of polyphenols (242.91 ± 68.93 µg GAE/mg), tannins (110.59 ± 11.31 µg TAE/mg) and flavonoids (26.74 ± 0.52 µg QE/mg). JPWT exhibited antioxidant activity with an IC50 of 17.05 ± 0.67 µg/mL in the DPPH assay and an EC50 of 75.81 ± 2.02 µg/mL in the FRAP assay, confirming its antioxidant activity. Antibacterial screening revealed dose-dependent inhibition, with stronger effects against Gram-positive strains. Molecular docking suggested that hydroxychavicol and 2,3-dehydroferruginol may contribute to antibacterial activity through favorable binding to MRSA PBP2a and ESBL CTX‑M‑15. Overall, these findings support JPWT as a promising natural source of antimicrobial and antioxidant agents and warrant further isolation and in vivo investigations.